De-risking Lending in Ghana’s Cocoa Sector to Promote Climate Smart Cocoa Adoption – Proposed Framework - Dalaa, Mustapha Alasan; Saeed, Abdul-Razak; Deffor, Eric Worlanyo; Kofituo, Rich Kofi; Asare, Richard (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Cocoa is important raw material to the global chocolate industry (Financial Times, 2015). Globally, between 40–50 million people depend on the cocoa sector for their livelihood (Beg et al., 2017). In Ghana, the crop remains a key source of foreign exchange and contributes about 13% to gross domestic product (GDP) (Aboah et al. 2019; Asubonteng et al., 2018). Export earnings from cocoa is about 30% (Monastyrnaya et al., 2016). In terms of employment close to 30 % of Ghana’s population derive their income from the sector’s Supply Chain (Anthonio and Aikins, 2009; Gockowski et al., 2011). To increase the output of cocoa, smallholders tend to engage in area expansion rather than intensification which leads to clearing of total forest (Jagoret, Deheuvels & Bastide, 2014). This practice has led to a significant reduction in the volume of forest cover in Ghana thereby rendering the sector susceptible to climate change effects. Although the cocoa sector faces hydra-headed challenges, climate change tends to increase the vulnerability of the smallholder farmer (Fountain & Huetz-Adams, 2018). Climate change is a phenomenon that has been taking place throughout history but over the last century it has accelerated, and scientists believe it is increasingly due to human activities (J. Cook, et al, April 2016). To ameliorate these challenges the smallholder farmer needs to adopt sustainable production systems that guarantee a decent livelihood for family farmers while avoiding practices that are detrimental to the environment (Amiel Lauran, & Muller, 2019).